Aplikasi Keamanan Berkas dengan Enkripsi AES dan Biometrik Sidik Jari Berbasis Android - Habib Husain Amirullah; Ade Eviyanti; Sumarno Sumarno (LPPM STIKI MALANG, 2024)
Data security in the current digital era has become critically important. Data and digital document thefts continue to occur, with an average cost of 3.86 million due to data breaches in 2018. To tackle this challenge, cryptography, particularly encryption, has become a key element in maintaining data confidentiality and integrity. The Advanced Encryption Standard (AES) has become the global standard for preserving data confidentiality by transforming data into a form that is difficult to decipher without the correct key. However, AES security relies heavily on the strength of the key used, posing risks of weak keys and potential negligence. This research aims to address these issues by combining AES-128 as the encryption algorithm and fingerprint-based authentication to enhance security access. The use of fingerprint biometric verification provides a user-friendly layer of security. The application was tested using Automated Testing, which is a method for testing a system using a series of scripts. The test results demonstrate that by combining the latest encryption technology and biometric authentication, this research successfully developed an application capable of encrypting data using the AES algorithm and integrating it with BiometricPrompt. The outcome is an improved level of data security in this digital era.